1989
DOI: 10.1007/bf01958273
|View full text |Cite
|
Sign up to set email alerts
|

Possible association of sudden infant death with partial complement C4 deficiency revealed by post-mortem DNA typing of HLA class II and III genes

Abstract: Based on evidence of an increased rate of respiratory infections in sudden infant death (SID) infants as well as the observation of familial occurrence, we analysed in a retrospective study class II and class II genes of the major histocompatibility complex in 40 cases of SID by Southern blot analysis of DNA obtained post mortem from tissue samples. In 24 cases, the parents were interviewed and confirmatory human lymphocyte antigen (HLA) and DNA typing was carried out. Using HLA-DR beta and -DQ beta probes, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 32 publications
1
20
0
1
Order By: Relevance
“…The first SIDS candidate genes that were investigated in relation to the immune system response to infection were in the major histocompatibility complex (HLA in humans, chromosome 6p). HLA-DR2 was decreased in 39 SIDS cases versus controls [Keller et al, 1990], but this relationship was not confirmed in two other studies (40 SIDS cases, Schneider et al, 1989;39 SIDS cases, Kaada and Spurkland, 1992). The C4 gene (also involved in the immune system and in linkage disequilibrium with HLA) [O'Neill et al, 1978] has also been investigated with SIDS.…”
Section: Infection/inflammation Genes In Sidsmentioning
confidence: 94%
See 1 more Smart Citation
“…The first SIDS candidate genes that were investigated in relation to the immune system response to infection were in the major histocompatibility complex (HLA in humans, chromosome 6p). HLA-DR2 was decreased in 39 SIDS cases versus controls [Keller et al, 1990], but this relationship was not confirmed in two other studies (40 SIDS cases, Schneider et al, 1989;39 SIDS cases, Kaada and Spurkland, 1992). The C4 gene (also involved in the immune system and in linkage disequilibrium with HLA) [O'Neill et al, 1978] has also been investigated with SIDS.…”
Section: Infection/inflammation Genes In Sidsmentioning
confidence: 94%
“…There are two isotypes of C4, C4A and C4B; C4A preferentially reacts with amino groups to form amide bonds and C4B preferentially binds hydroxyl groups to form ester bonds [Law et al, 1984]. Schneider et al [1989;40 SIDS cases], Keller et al [1990;39 SIDS cases], and Opdal et al [1994;61 SIDS cases] found increases in C4B deletions in SIDS cases versus controls that were not statistically significant overall, but in the Schneider et al [1989] and Opdal et al [1994] studies the increases were significant in subsets of cases that had evidence of recurrent infections [Schneider et al, 1989] (P ¼ 0.01 for C4B deletions) or signs of infection prior to death [Opdal et al, 1994] (P ¼ 0.03 for C4A and C4B deletions). Opdal et al [1999b] then investigated C4 in 104 SID cases (89 totally unexplained SIDS plus 15 borderline SID), 52 with and 52 without slight infections prior to death; and 84 living infants, 22 with and 62 without infection.…”
Section: Infection/inflammation Genes In Sidsmentioning
confidence: 99%
“…Partial deletions of the complement factor 4 (C4) gene in combination with slight upper airway infections have been related to an increased risk for SIDS [152][153][154] .…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…32 The C4 gene was investigated among both German and Norwegian SIDS victims (40 and 104 cases, respectively), but neither of the studies detected any differences between SIDS cases and control cases with respect to gene frequencies. 33,34 However, both studies revealed an association between slight infections before death and partial deletions of either the C4A or C4B gene, which may indicate that this combination indicates increased risk of sudden infant death.…”
Section: C4mentioning
confidence: 96%